BASLAWÍSH KLASSLARDA MATEMATIKA PÁNINEN KLASSTAN TÍS JUMÍSLARDÍ SHÓLKEMLESTIRIW METODIKASÍ - Nagmetova, N.M. (SCIENCE and SOCIETY, 2023)
This article talks about the methodology of organizing extracurricular activities in mathematics in primary grades. Class works on the use of TRIZ technology are shown in mathematics circles in primary grades.